Dominance and competition: a giving-up density analysis of rank-based foraging decisions of small groups of confined bison (Bison bison) - Loncar, Marin (My University, 2023)
Socially foraging animals such as bison (Bison bison) modify their foraging behaviour based on social status and food availability to maximize individual fitness. Winter feeding trials were performed on juvenile bison at Stanley Hill Bison Farm in Kakabeka Falls, ON, using a giving-up density (GUD) framework to record the densities of a resource at which bison of various rank would cease foraging. Bison were provided with two food sources, abundant lower-quality hay and limited higher-quality oats mixed with blocks of wood in feeding trays. Time spent foraging from the high-quality trays by each bison, as well as all instances of voluntary quitting and involuntary abandonments of patches, were recorded and compared to the density of food remaining in the trays at the end of the trials. Rank was negatively related to GUDs, with high-ranked bison ceasing foraging at the lowest GUDs. Dominants prematurely abandon their own trays in favour of subordinates. However, lower-ranked bison forage for a shorter time from the oats and cease foraging altogether at higher GUDs to exploit lower-quality hay, likely to escape competition as the costs of foraging from the oats increased. Males may also have a lower GUD than females. That high- and low-ranked captive bison use different strategies of foraging in confined environments supports the widely acknowledged theory that social rank has a large effect on foraging behaviour and energetic intake, and the results of the trials quantify this through difference. This study highlights the existence of two feedback loops: (1) a positive loop where increased foraging efficiency reinforces rank for high-ranked bison, and (2) a negative loop whereby low-ranked bison are forced to forage inefficiently and are thus ever more disadvantaged against competition from higher-ranked bison.
Keywords: Bison foraging ecology; Bison (foraging behaviour)